Rectification effects of regional air–sea interactions over western boundary current on large-scale sea surface temperature and extra-tropical storm tracks - Lionel Renault; Thomas Arsouze; Fabien Desbiolles; Justin Small (Scientific Reports)
Abstract The warm Western Boundary Currents (WBCs) and their zonal extensions are persistent, deep, strong and narrow oceanic currents. They are known to anchor and energize the Extra-Tropical storm tracks by frontal thermal air–sea interactions. However, even in the latest generation of climate models, WBCs are characterized by large biases, and both the present storm-track activity and its recent intensification are poorly estimated. Mesoscale air–sea interactions, and in particular the Current Feedback to the Atmosphere (CFB) have been shown to be important in ocean and in particular WBC dynamics as they modify the energy budget of the ocean. CFB causes eddy-killing by drag friction between currents and the atmosphere. It damps the oceanic eddy activity, and, thus, weakens the eddy-mean flow interaction, stabilizing WBCs. Based on cutting-edge high-resolution coupled global simulations, we show that the stabilization of WBCs by CFB modulates the mean Sea Surface Temperature and its meridional gradients as well and the turbulent heat fluxes between the ocean and the atmosphere. This alters the baroclinicity of the lower atmosphere, which in turn modulates the extra tropical storm-tracks intensity by up to 15%.